2015
DOI: 10.2105/ajph.2014.302263
|View full text |Cite
|
Sign up to set email alerts
|

Identifying a Sample of HIV-Positive Beneficiaries From Medicaid Claims Data and Estimating Their Treatment Costs

Abstract: Objectives We sought to identify people living with HIV/AIDS (PLWHA) from Medicare and Medicaid claims data to estimate Medicaid costs for treating HIV/AIDS in California. We examined how alternate methods of identifying the relevant sample affect estimates of per capita costs. Methods We analyzed data on Californians enrolled in Medicaid with an HIV/AIDS diagnosis reported in 2007 Medicare or Medicaid claims data. We compared alternative selection criteria by examining use of antiretroviral drugs, HIV-speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 13 publications
1
22
0
Order By: Relevance
“…In addition, the treatment cost of patients with a CD4 level of <100 cell/mm 3 was two-fold higher than that of patients with a CD4 level of 100-300 cell/mm 3 or >300 cell/ mm 3 . These findings are similar to those reported in the international literature [10][11][12][13][14][15][16][17]. A limitation of the present study is the study sample, which consisted of patients who attended a university hospital.…”
Section: Analysis Of the Treatment Costs Of Hiv/aids In Turkeysupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, the treatment cost of patients with a CD4 level of <100 cell/mm 3 was two-fold higher than that of patients with a CD4 level of 100-300 cell/mm 3 or >300 cell/ mm 3 . These findings are similar to those reported in the international literature [10][11][12][13][14][15][16][17]. A limitation of the present study is the study sample, which consisted of patients who attended a university hospital.…”
Section: Analysis Of the Treatment Costs Of Hiv/aids In Turkeysupporting
confidence: 91%
“…Another analysis based on Medicaid claims in the state of California reported that the medical cost per patient was $ 36,469 [12]. The cost of HIV treatment per patient was estimated to be € 11,638, € 32,110, € 14,821, € 6,399, and € 25,340 in Spain, Germany, France, Italy, and the U.K. respectively [13].…”
Section: Resultsmentioning
confidence: 99%
“…[1] Leibowitz and Desmond, analyzing 2007 Medicaid data from California, also limited analyses to those in Medicaid FFS care and excluded those in managed care plans or those enrolled in Medicare. [13] They estimated per capita FFS Medicaid expenditures for medical and pharmaceutical claims to be $36,469. In the current study, the mean Medicaid FFS payment for medical care in 2007, without inflation adjustment, was comparable: $34,318 (n=2,543).…”
Section: Discussionmentioning
confidence: 99%
“…An algorithm that required an HIV diagnosis in two outpatient claims or one inpatient claim was used to identify adult beneficiaries with strong evidence of HIV. 27 Our analyses included only fee-for-service Medicare and Medicaid enrollees because available data for Medicare managed care enrollees lack diagnosis fields needed to confirm HIV status. Medicaid-only beneficiaries (not dually enrolled in both Medicaid and Medicare) with visits to federally qualified health centers or rural health centers were excluded due to limited coding of procedures in these claims.…”
Section: Datamentioning
confidence: 99%